Evolutionary ecology of microsporidia associated with the invasive ladybird Harmonia axyridis. (26th November 2014) - Vilcinskas, Andreas; Schmidtberg, Henrike; Estoup, Arnaud; Tayeh, Ashraf; Facon, Benoit; Vogel, Heiko
Abstract Invasive species are characterized by the rapid growth and spread of their populations after establishing a foothold in new habitats, and there are now many examples of such species negatively affecting biodiversity and the economy. It is unclear why some species can become successful invaders, whereas most (even if closely related) remain noninvasive. We previously proposed a hypothesis that parasites associated with invading species can promote their invasive success if they are harmless toward the invaders but harmful to their competitors and/or predators in the newly colonized habitat. Here we discuss whether microsporidia that have recently been discovered in the invasive ladybird Harmonia axyridis contribute to its invasive success. We show that all H. axyridis beetles sourced from diverse collection sites all over the world carry abundant microsporidia. This suggests that both native and invasive H. axyridis populations are associated with these tolerated parasites, which were likely to have existed in native populations before expansion rather than being acquired in newly colonized areas. We describe the pathogenesis of the microsporidia during different developmental stages of H. axyridis and we address the possibility that the predation of its infected eggs and larvae by competing native ladybird species may lead to their infection and ultimately to their decline. Finally, we discuss our initial hypothesis: microsporidia that are tolerated by an invasive vector insect can be active against susceptible native competitors and/or predator species.